2014
DOI: 10.1016/j.jmoldx.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Extra Alleles in FMR1 Triple-Primed PCR

Abstract: Triple-primed PCR assays have become the preferred fragile X syndrome testing method. Using a commercially available assay, we detected a reproducible extra peak(s) in 0.5% of 13,161 clinical samples. The objectives of this study were to determine the cause of these extra peaks; to identify whether these peaks represent an assay specific artifact, an underlying chromosome aneuploidy, or somatic mosaicism; and to ascertain their clinical relevance. The presence of an extra allele(s) was confirmed by a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
3
3
1
Order By: Relevance
“…While somatic instability of premutation and full mutation alleles is well documented ( Cambouris et al, 1996 ; Dobkin et al, 1996 ; Mingroni-Netto et al, 1996 ), information regarding unstable normal alleles ( Sullivan et al, 2005 ; Nolin et al, 2011 ) is limited. In contrast to the report of Wakeling et al (2014) , Maia et al (2017) reported on four FXS mosaic males carrying normal, premutated and full mutation FMR1 alleles. The authors suggested that the normal allele of these patients resulted from postzygotic contraction of the full expansion.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…While somatic instability of premutation and full mutation alleles is well documented ( Cambouris et al, 1996 ; Dobkin et al, 1996 ; Mingroni-Netto et al, 1996 ), information regarding unstable normal alleles ( Sullivan et al, 2005 ; Nolin et al, 2011 ) is limited. In contrast to the report of Wakeling et al (2014) , Maia et al (2017) reported on four FXS mosaic males carrying normal, premutated and full mutation FMR1 alleles. The authors suggested that the normal allele of these patients resulted from postzygotic contraction of the full expansion.…”
Section: Discussioncontrasting
confidence: 70%
“… Sharony et al (2012) , Wakeling et al (2014) , and also our laboratory (data not shown) experienced instability/mosaicism in the normal–intermediate range (less than 55 CGG repeats). Wakeling et al (2014) reported that about 0.4% of the normal population tested showed an extra allele.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition, if these two cases have small population sizes of mosaicism, it can be detected by TP-PCR but not by FA. These results are similar to previously reported cases demonstrating different results for FA and TP-PCR, which were attributed to different DNA amounts [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…First, allele expansion occurs mainly during maternal but not paternal transmission, regardless AGG loss or CGG repeat length. Second, although FMR1 allelic mosaicism is generally characterized by the presence of a premutation and a full mutation alelle, it has been reported also within the normal CGG repeat range (3 alleles of different sizes) regardless AGG loss (Sharony et al, ; Wakeling, Nahhas, & Feldman, ). Indeed, in this study we report cases with AGG loss in both alleles in the normal CGG repeat length which appears to be in contrast with the expectation that the loss of AGG interruptions causing CGG repeat instability.…”
Section: Introductionmentioning
confidence: 99%